Concise total synthesis of AB5046A and AB5046B. Issue 18 (2nd May 2018) - Kong, Lu-Yao; Cui, Qing; Jin, Zhong; Xu, Xiao-Hua
Graphical abstract: An efficient total synthesis of naturally occurring 5-oxo β-triketones, AB5046A and AB5046B, was achieved utilizing the commercial available phloroglucinol as a starting material. Highlights: Total synthesis of two naturally occurring rare 5-oxo β-triketones. Five linear steps with high overall yields for AB5046A and AB5046B. Practical preparation of 3-ethoxy-5-hydroxycyclohex-2-enone from phloroglucinol. Abstract: Two naturally occurring rare 5-oxo β-triketones, AB5046A and AB5046B, were efficiently synthesized in five linear steps with overall yields of 36% and 28%, respectively. The synthetic strategy highlighted the readily preparation of the key intermediate, 3-ethoxy-5-hydroxycyclohex-2-enone, from commercially available phloroglucinol.